RELATIONSHIP BETWEEN HRM PRACTICES AND PERCEIVED ORGANISATIONAL PERFORMANCE THROUGH THE LENS OF WORK ATTITUDES: EVIDENCE FROM RURAL BANKS (IITM Journal of Business Studies, 2024)
Purpose: The purpose of this paper is to  understand the relationship between HRM  practices and Perceived Organisational  Performance (POP) and also examine the role  of employee work attitudes as mediator in  influencing such relationship. Design/Methodology/Approach: Following  a descriptive research design, an empirical  investigation was carried out by approaching  300 respondents from regional rural banks in  India to collect data through online survey forms  as well as physical questionnaires. The research  instruments was developed using five-point  Likert-type scale and items for the construct in  the study were taken based on literature review.  The SPSS 21.0 and AMOS 21.0 were used for  data analysis and hypothesis testing. Findings: It was found that HRM practices  are positively related with organisational  performance. In addition to this it was also  revealed that work attitudes partially mediate  the HRM-OP relationship. Originality/Value: The study is original in  the sense that it provides insights into HRM  practices and Organisational Performance  relationship through the lens of work attitudes  in regional rural banks. Implication: The study would be helpful for  the concerned authorities in understanding  HRM-PERFORMANCE mechanism,  redesign HRM policies as employee centric,  focus on social exchange relationship in  an organisation to improve organisational  performance. Management could think of  providing department wise training so that  employees could focus towards their specific  department.
Keywords: Human Resource Management (HRM) Practices; Work Attitudes (Job Involvement & Organisational Commitment); Perceived Organisational Performance (POP); Rural Banks